PENDIDIKAN FIQIH IBADAH DALAM KITAB SABILAL MUHTADIN KARYA SYEKH MUHAMMAD ARSYAD AL-BANJARI - Ahmad Syihabudin; Uwandi Uwandi; Sarbendi Sarbendi (STAI Darul Qalam Tangerang, 2026)
Fiqh worship education is an effort to provide learning about fiqh of worship, namely about how to establish a worship in Islam in accordance with the provisions of sharia. One of the monumental books and still a reference for fiqh, especially in the Southeast Asian region, is the Book of Sabilal Muhtadin by Sheikh Muhammad Arsyad Al-Banjari. The book contains a detailed explanation of the provisions of fiqh in Islam that are adapted to the situation and conditions of the people of Kalimantan. Therefore, the researcher is interested in studying the fiqh education of worship contained in the Book of Sabilal Muhtadin by Sheikh Muhammad Arsyad Al-Banjari. This research aims to examine the educational process of worship fiqh and examine the purpose of worship fiqh education in the Book of Sabilal Muhtadin by Sheikh Muhammad Arsyad Al-Banjari. This research is a library research with a qualitative approach. Primary data include the general concept of worship fiqh, the concept of worship fiqh education and the study of Banjar as a culture. The secondary data is a brief biography of Sheikh Muhammad Arsyad Al-Banjari and a general description of the Book of Sabilal Muhtadin. Data collection techniques include Documentary Studies and Literature Studies. Data processing techniques include descriptive methods, data classification editing, and data interpretation. The results of the research obtained that the fiqh education of worship contained in the book of Sabilal Muhtadin can be understood from the description of Sheikh Muhammad Arsyad Al-Banjari's explanation of fiqh. The purpose of worship fiqh education includes providing a deep understanding of fiqh to the community, opening the public's view of true worship in Islam, expanding the community's insight and knowledge about worship fiqh, answering the community's problems in carrying out Islamic law, eliminating superstitious beliefs. The process of religious fiqh education that occurs can be seen from the change in the behavior and knowledge of the people of South Kalimantan about religious fiqh after studying the Book of Sabilal Muhtadin.